Essential Kierkegaard. - Kierkegaard, Søren, 1813-1855 (Princeton University Press, 2013)
This is the most comprehensive anthology of Søren Kierkegaard's works ever assembled in English. Drawn from the volumes of Princeton's authoritative Kierkegaard's Writings series by editors Howard and Edna Hong, the selections represent every major aspect of Kierkegaard's extraordinary career. They reveal the powerful mix of philosophy, psychology, theology, and literary criticism that made Kierkegaard one of the most compelling writers of the nineteenth century and a shaping force in the twentieth. With an introduction to Kierkegaard's writings as a whole and explanatory notes for e.